计算:2x2•3xy=______.
2x2•3xy=2×3x2•x•y=6x3y.
举一反三
- 分解因式()x()3()y()-()2()x()2()y()2()+()xy()3()正确的是A.()xy()(()x()+()y())()2()B.()xy()(()x()2()﹣()2()xy()+()y()2())()C.()xy()(()x()2()+2()xy()﹣()y()2())()D.()xy()(()x()﹣()y())()2
- 设\(z = u{e^v}\),\(u = {x^2} + {y^2}\),\(v = xy\),则\( { { \partial z} \over {\partial y}}=\)( )。 A: \({e^{xy}}({x}y^2 + {x^3} + 2y)\) B: \({e^{xy}}({x^2}y + {x^3} + 2y)\) C: \({e^{xy}}({x}y^2 + {x^3} + 2x)\) D: \({e^{xy}}({x}y+ {x^3} + 2y)\)
- 设\(z = u{e^v}\),\(u = {x^2} + {y^2}\),\(v = xy\),则\( { { \partial z} \over {\partial x}}=\) A: \({e^{xy}}({x^2}y + {y^3} + 2x)\) B: \({e^{xy}}({x}y^2 + {y^3} + 2x)\) C: \({e^{xy}}({x}y + {y^3} + 2x)\) D: \({e^{xy}}({x^2}y + {y^2} + 2x)\)
- 9. 已知函数$z=z(x,y)$由${{z}^{3}}-3xyz={{a}^{3}}$确定,则$\frac{{{\partial }^{2}}z}{\partial x\partial y}=$( ) A: $\frac{z({{z}^{4}}-2xy{{z}^{2}}-{{x}^{2}}{{y}^{2}})}{{{({{z}^{2}}-xy)}^{3}}}$ B: $\frac{z({{z}^{4}}-2xy{{z}^{2}}-xy)}{{{({{z}^{2}}-xy)}^{2}}}$ C: $\frac{z({{z}^{3}}-2xyz-{{x}^{2}}{{y}^{2}})}{{{({{z}^{2}}-xy)}^{3}}}$ D: $\frac{z({{z}^{3}}-2xy{{z}^{2}}-{{x}^{2}}y)}{{{({{z}^{2}}-xy)}^{3}}}$
- 方程\( xy'' - 5y' + 3xy = {\cos ^2}x \)的通解中包含 (写数字)个独立的任意常量。______
内容
- 0
计算:(-2a).(2a^2-3a+1)3x^2.(-3xy)^2-x^2(x^2y^2-2x)
- 1
lim(x→0)(3xy/(x^2+y^2))
- 2
计算(1)(x+3)(2x2一4x+1)(2)(3x3一2x+1)(2-x)(3)3(x一2)(x+1)一2(x一5)(x-3)(4)x(x2一4)一(x+3)(x2一3x+2)
- 3
计算(xy的2次方+3)(xy的2次方)-2x(-x+y)
- 4
积分[img=136x52]1803d6afd4e6f95.png[/img]的计算程序和结果是 A: clearsyms xy=1/x^2/sqrt(x^2-1)int(y,x,-2,-1)3^(1/2)/2 B: clearsyms xint(1/x^2/sqrt(x^2-1),x,-2,-1)3^(1/2)/2 C: clearsyms xint(1/x/sqrt(x^2-1),x,-2,-1)-pi/3 D: clearsyms xint(1/x/sqrt(x^2-1),x,-2,-1)3^(1/2)/2 E: clearsyms xint(1/x^2*sqrt(x^2-1),x,-2,-1)log(3^(1/2) + 2) - 3^(1/2)/2